Ukugula Kwabantu: the construction of mental health by traditional healers in a peri-urban area.1 - Makanya, Sinethemba (My University, 2021)
This thesis explores the question “How do traditional healers construct mental health?” It is concerned with understanding African ways of viewing health and disease which are inextricably linked to the nature of knowledge as shared and negotiated, within the African cosmology. This thesis challenges a foregrounding of theories imported from the global North and the perceived and imposed superiority of biomedicine. I argued that as a contextual starting point, an orientation into the worldview of a traditional healer is imperative to locate the study within the context of a peri-urban area such as Chiawelo in Soweto as a case study. I used qualitative phenomenological interviews with traditional healers in and around Chiawelo as well as an autoethnography of my own initiation into traditional healing to counter my researcher bias and afford me the opportunity to think from the worldview of a traditional healer. I examined the African cosmological view of reality to arrive at an understanding of how reality, knowledge, and the human are conceived of within African metaphysics. These notions informed the theoretical framework through which to enter the worldview of a traditional healer. An exploration of how knowledge is transmitted within the training of the traditional healer gave a practical view of how material and immaterial realities interface within the African cosmological view of reality. This gave insight into the nature of the relationships between various sites of knowledge or key stakeholders within traditional healing. Examining the traditional healer provided a case study of the processes within the human, thereby providing an account of the nature of the human. Finally, I examined notions of disease causation within this cosmological view of reality and isolated categories that construct traditional healers’ understandings of health or more specifically of mental health. I found that mental health within traditional healing is thus constructed in relation to a general category of health and in relation to an expanded view of the human. I argued that while the notion of mental health is essentially a Euro-American construct, it is implicitly considered in traditional healing interventions. The health of an individual is constructed across spiritual, psycho-spiritual, psychosocial, ecological, and physiological domains of existence. These categories are deeply entangled in one another, and traditional healers engage in the comprehensive and systematic assessment of the health (or ill-health) of their patients. Furthermore, traditional healers acknowledge the boundaries of their practices and show a willingness to refer should treatment fall outside the boundaries of their expertise. It is upon these boundaries that collaboration with other mental health care workers can occur, and a system of integration proposed.
A thesis submitted in fulfilment of the requirements for the Doctor of Philosophy to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, 2021